2019
DOI: 10.4314/tjpr.v18i1.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin K2 on bone mineral density and serum cathepsin K in female osteoporosis patients

et al.

Abstract: Purpose: To investigate the influence of vitamin K2 on bone mineral density, bone metabolism and serum tissue protease K (cathepsin K) in female patients with osteoporosis. Method: A total of 210 osteoporosis patients in Affiliated Hospital of Nanjing University of Chinese Medicine who met the inclusion criteria were selected from January 2017 to January 2018. The patients were randomly divided into vitamin K2 group, strontium renate group and blank control group (70 patients/group). Strontium ranelate group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Osteocalcin was main non-collagenous protein produced by osteoblasts and levels were increased at 24 weeks after fracture of the tibial shaft. 32 Yuanyang et al 32 investigated the effect of vitamin K2 on bone mineral density in female patients with osteoporosis and they found that appropriate vitamin K2 treatment improves bone mineral density in the hip and waist of women with osteoporosis and PINP levels were increased in vitamin K2 treatment in these group. In our study, a remarkable increase was found in biomarkers of bone metabolism such as osteocalcin, PINP, and PICP compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin was main non-collagenous protein produced by osteoblasts and levels were increased at 24 weeks after fracture of the tibial shaft. 32 Yuanyang et al 32 investigated the effect of vitamin K2 on bone mineral density in female patients with osteoporosis and they found that appropriate vitamin K2 treatment improves bone mineral density in the hip and waist of women with osteoporosis and PINP levels were increased in vitamin K2 treatment in these group. In our study, a remarkable increase was found in biomarkers of bone metabolism such as osteocalcin, PINP, and PICP compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…This correlated with an increase in osteogenic activity, therefore providing evidence that the risk of osteoporotic fracture can be reduced through nutritional supplements, specifically vitamin K 2 . However, the effect of vitamin K 2 on increasing BMD and reduced osteoclast activity was relatively small when compared to other standard medications, such as strontium ranelate of the supplements used in the study; strontium ranelate was shown to express the highest increase in BMD while also reducing osteoclast activity [ 28 ].…”
Section: Metabolism Of Calciummentioning
confidence: 99%